The Influence of the Use of Code-Mixing in Teaching by English Teachers (Perspectives from EFL Teenage Students) - Kesha Karinadhira; Anita Dewi Ekawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Teaching English to EFL students is a challenge for English teachers in Indonesia, where English is viewed as a foreign language. Teachers in Indonesia often use code-mixing to facilitate better understanding of the lessons among students and to help them follow the material easily. However, the use of code-mixing itself must be carefully considered to ensure students can also practice their English specifically. Therefore, the objective of this study is to ascertain whether English teachers’ classroom instructions are affected by the use of code-mixing, and if so, whether code-mixing can positively affect English learning in schools. For instance, code-mixing helps them enhance their understanding of the material. This quantitative study collected data through an online questionnaire and was conducted on EFL teenage students in Indonesia. In this study, data were collected from 165 EFL teenage students in Indonesia through a closed-ended Likert-scale questionnaire. The data were then analyzed using Regression Analysis, which showed a significant impact (Sig. = 0.000, p < 0.05). The findings indicate that code-mixing impacted students’ perception of English language learning with their teachers. It helped them understand the material, develop language skills, and make them feel more confident.